Stoneheart - Fletcher, Charlie, 1960- (New York : Hyperion Paperbacks for Children, 2008)
When twelve-year-old George accidentally decapitates a stone statue in London, England, he falls into a parallel dimension where he must battle ancient "live" statues and solve a dangerous riddle
Originally published: U.K. : Hodder Children's Books, c2006
Keywords: Statues -- Fiction; Fantasy fiction